A Malay language cross cultural adaptation of the Boston Carpal Tunnel Questionnaire in the Malay speaking population seeking treatment at Hospital Tengku Ampuan Afzan, Kuantan - Sazli bin Mohd Nor (Kulliyyah of Medicine, International islamic University Malaysia, 2018)
The objective of this thesis was to translate the English language Boston Carpal Tunnel Questionnaire, a self-administered assessment tool as an instrument to evaluate the functional and symptomatic status of a carpal tunnel syndrome patient, another objective is to ensure its cultural equivalence in the Malay language for the Malay speaking population of Malaysia, which was done at Hospital Tengku Ampuan Afzan from 2014-2015. The internal consistency was analysed using Chronbach's Alpha coefficient, comparing the Symptom Severity Score and Functional Severity Score. Its reliability was measured using paired t-test between a period of 1-3 weeks between retest. The internal consistency and reliability were found to be acceptable.